Emissions of volatile organic compounds from Norway spruce and potential atmospheric impacts - Hakola, Hannele; Taipale, Ditte; Praplan, Arnaud; Schallhart, Simon; Thomas, Steven; Tykkä, Toni; Helin, Aku; Bäck, Jaana; Hellén, Heidi (Frontiers in Forests and Global Change, 2023)
Published biogenic volatile organic compound (BVOC) emission rates of Norway spruces vary a lot.In this study we combined published Norway spruce emission rates measured in boreal forests (Meeningen et al., 2017; Bourtsoukidis et al., 2014a, 2014b; Hakola et al., (2003, 2019)) and added our new, unpublished emission data from southern (SF) and northern Finland (NF). Standardised summer monthly mean emission potentials of isoprene vary from below the detection limit to 7 µg g-1(dw) h-1, and monoterpene (MT) and sesquiterpene (SQT) emission potentials 0.01–3 µg g-1(dw) h-1 and 0.03-2.7 µg g-1(dw) h-1, respectively. In this study, we found much higher SQT emissions from Norway spruces than previously measured and on average SQTs had higher emission potentials than isoprene or MTs. The highest monthly mean SQT emission potential of 13.6 µg g-1(dw) h-1 was observed in September in southern Finland. We found that none of the younger (33-40 years) trees in Hyytiälä, southern Finland, emitted isoprene, while one 50-year-old tree was a strong isoprene emitter. The difference due to age could not be confirmed, since all measured small trees were growing in Hyytiälä, so this could also be due to the same genetic origin. On average, older trees (>80 years) emitted about ten times more isoprene and MTs than younger ones (<80 years), but no clear difference was seen in SQT emissions. SQT emissions can be more related to stress effects. As shown here for Norway spruce, it is possible that the emission factor of SQTs is significantly higher than what is currently used in models, which may have significant effects on the prediction of formation and growth of new particles, since the secondary organic aerosol (SOA) formation potential of SQTs is high, and this may have significant effects on the formation and growth of new particles. Due to the high secondary organic aerosol (SOA) formation potentials of SQTs, the impact on SOA formation and mass could be even higher.